HYDROCARBON SHALE POTENTIAL IN TALANG AKAR AND LAHAT FORMATIONS ON SOUTH AND CENTRAL PALEMBANG SUB BASIN - Julikah Julikah; Sriwidjaya Sriwidjaya; Jonathan Setyoko Hadimuljono; Panuju Panuju (Scientific Contributions Oil and Gas, 2015)
South and Central Palembang Sub - basin over Talang Akar (TAF) and the Lemat/Lahat Formations (LEF/LAF) has shale hydrocarbons (HC shale) which are considerably promising. Seismic interpretation results shows potential HC shale scattered in several areas around the Rukam-1, Kemang-1, Lion-1 and Tepus-1 wells. Generally, thermal modeling results indicates early maturity of oil on the value of Ro = 0.6% at about 2000 m depth (h), the formation of oil on the value Ro = (0.7-0.9)% at between (2200 £ h <3100) m depth and formation of gas at Ro values between (0.9-1.2)% at a depth between (3100-3500)m. Talang Akar and Lahat/Lemat Formations have a shallow marine depositional environment with Type II/III kerogen and lacustrine with Type III kerogen. Based on advanced seismic data processing (a method of seismic attributes and spectral decomposition) these areas are expected to have a TOC>2% value that qualifies as shale HC. The assessment (P-50) of potential non-conventional oil and gas resources at Talang Akar and Lahat/Lemat Formations is estimated to be fairly large (up to 4200 MMBOE).